PRODUKSI IgA & IgG MUKOSAL DAN SISTEMIK SETELAH IMUNISASI PER ORAL DENGAN PROTEIN AdhO36 SALMONELLA TYPHI PADA MENCIT BALB/C - Santoso, Sanarto (Jurnal Kedokteran Brawijaya, 2003)
ABSTRACT An experiment has been conducted to determine the production of mucosal and systemic IgA and IgG after oral immunization with AdhO36 protein Salmonella typhi using CTB as adjuvant. The results of ELISA Test, shows that AdhO36 protein Salmonella typhi were highly significantly (p = 0.001) able to induce the production of S-IgA (secretory IgA), as compared to control and CTB treatment. The analysis of variance results show that the effect of AdhO36 protein to the IgA content in serum is high significantly different to IgA content in mucus (p=0.001). This finding is relevant to the previous experiments that the oral administration of AdhO36 protein can inhibit the in vivo adhessive process of Salmonella typhi at enterocytes of Balb/c mice. Therefore, it can be concluded that AdhO36 protein  Salmonella  typhi  is  a  potential  mucosal  immunogen  which  can  induce  mucosal  immune  response  as  the  results  of  the formation of protective S-IgA, which in turn, can inhibit the adhesive process as the initial stage of infection process at enterocytes of Balb/c mice.  Apart from S-IgA,